2010
DOI: 10.1016/j.neuron.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of GABAARs to Synapses Is Mediated by HAP1-KIF5 and Disrupted by Mutant Huntingtin

Abstract: The density of GABAA receptors (GABAARs) at synapses regulates brain excitability, and altered inhibition may contribute to Huntington’s disease, which is caused by a polyglutamine repeat in the protein huntingtin. However, the machinery that delivers GABAARs to synapses is unknown. We demonstrate that GABAARs are trafficked to synapses by the kinesin family motor protein 5 (KIF5). We identify the adaptor linking the receptors to KIF5 as the huntingtin associated protein 1 (HAP1). Disrupting the HAP1-KIF5 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
262
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 226 publications
(271 citation statements)
references
References 46 publications
8
262
1
Order By: Relevance
“…We specifically focused on Kif5C and Kif3A kinesin complexes and have identified several proteins that are potentially targeted to synapses. Previous studies identified some cargos of Kif5C, including GABA receptors (22), axonal synaptic vesicle precursors (23), APP-containing vesicles (24,25), TrkB vesicles (26), mitochondria (23,(27)(28)(29)(30)(31), AMPAR vesicles (32), and mRNA/protein complexes (33,34). Kif3 was shown to transport fodrin-associating vesicles in cultured superior cervical ganglion neurons (35), Ncadherin in the developing mouse brain (36) and axonal voltagegated potassium channel in cultured hippocampal neurons (37).…”
Section: Discussionmentioning
confidence: 99%
“…We specifically focused on Kif5C and Kif3A kinesin complexes and have identified several proteins that are potentially targeted to synapses. Previous studies identified some cargos of Kif5C, including GABA receptors (22), axonal synaptic vesicle precursors (23), APP-containing vesicles (24,25), TrkB vesicles (26), mitochondria (23,(27)(28)(29)(30)(31), AMPAR vesicles (32), and mRNA/protein complexes (33,34). Kif3 was shown to transport fodrin-associating vesicles in cultured superior cervical ganglion neurons (35), Ncadherin in the developing mouse brain (36) and axonal voltagegated potassium channel in cultured hippocampal neurons (37).…”
Section: Discussionmentioning
confidence: 99%
“…Rat hippocampal neurons were prepared and cultured from embryonic day 18 rat brains. Cells were transfected by Amaxa nucleofection as previously described (35). See SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagosome transport is regulated by huntingtin (Wong and Holzbaur, 2014a), a scaffolding protein that binds dynein directly (Caviston et al, 2007) and also interacts with dynactin (p150 Glued subunit) and kinesin through Huntingtin-associated protein 1 (HAP-1) (Engelender et al, 1997;Li et al, 1995;Li et al, 1998;McGuire et al, 2006;Twelvetrees et al, 2010). Huntingtin localizes to the outer membrane of autophagosomes (Atwal et al, 2007;Martinez-Vicente et al, 2010) and regulates autophagosome transport through its interactions with dynein and HAP-1 (Wong and Holzbaur, 2014a).…”
Section: Box 2 Regulation Of the Axonal Transport Of Autophagosomesmentioning
confidence: 99%